Vitamin C therapy for patients with sepsis or septic shock: a protocol for a systematic review and a network meta-analysis - Toshi A Furukawa; Yasushi Tsujimoto; Georgia Salanti; Rinaldo Bellomo; Tomoko Fujii; Alessandro Belletti; Anitra Carr; Nora Luethi; Alessandro Putzu; Chiara Sartini; Andrew A Udy; Paul J Young (BMJ Open)
Introduction Vasoplegia is common and associated with a poor prognosis in patients with sepsis and septic shock. Vitamin C therapy in combination with vitamin B1 and glucocorticoid, as well as monotherapy in various doses, has been investigated as a treatment for the vasoplegic state in sepsis, through targeting the inflammatory cascade. However, the combination effect and the relative contribution of each drug have not been well evaluated. Furthermore, the best combination between the three agents is currently unknown. We are planning a systematic review (SR) with network meta-analysis (NMA) to compare the different treatments and identify the combination with the most favourable effect on survival.Methods and analysis We will include all randomised controlled trials comparing any intervention using intravenous vitamin C, vitamin B1 and/or glucocorticoid with another or with placebo in the treatment of sepsis. We are interested in comparing the following active interventions. Very high-dose vitamin C (≥12 g/day), high-dose vitamin C (≥6 g/day), vitamin C (<6 g/day); low-dose glucocorticoid (<400 mg/day of hydrocortisone (or equivalent)), vitamin B1 and combinations of the drugs above. The primary outcome will be all-cause mortality at the longest follow-up within 1 year but 90 days or longer postrandomisation. All relevant studies will be sought through database searches and trial registries. All reference selection and data extraction will be conducted by two independent reviewers. We will conduct a random-effects NMA to synthesise all evidence for each outcome and obtain a comprehensive ranking of all treatments. We will use the surface under the cumulative ranking curve and the mean ranks to rank the various interventions. To differentiate between the effect of combination therapies and the effect of a component, we will employ a component NMA.Ethics and dissemination This SR does not require ethical approval. We will publish findings from this systematic review in a peer-reviewed scientific journal and present these at scientific conferences.PROSPERO registration number CRD42018103860.